General and concise asymmetric synthesis of sphingosine, safingol and phytosphingosines via tethered aminohydroxylation - Kumar, Pradeep; Dubey, Abhishek; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2010)
A novel, practical and efficient enantioselective synthesis of sphingoid bases, L-threo-[2S,3S]-sphinganine (safingol), L-threo-[2S,3S]-sphingosine, L-arabino-[2R,3S,4R] and L-xylo-[2R,3S,4S]-C(18)-phytosphingosine is described. The synthetic strategy features the Sharpless kinetic resolution and tethered aminohydroxylation (TA) as the key steps.